Visible Light Photocatalytic Synthesis of Tetrahydroquinolines Under Batch and Flow Conditions. Issue 37 (10th September 2020) - González‐Muñoz, Daniel; Nova‐Fernández, José Luis; Martinelli, Ada; Pascual‐Coca, Gustavo; Cabrera, Silvia; Alemán, José
Abstract : In this work, we describe the use of visible light and a photocatalytic system for the cyclization of iodoaryl vinyl derivatives to tetrahydroquinoline structures. The reaction proceeds under very mild conditions, tolerates different functional groups and more importantly, the method allows the synthesis of N ‐free tetrahydroquinolines from N ‐unprotected starting materials. In addition, the reaction can also be performed using flow‐chemistry. Finally, a mechanistic proposal based on some mechanistic studies has been described. Abstract : In this work, we have found an effective method for the cyclization of aryl‐iodine derivatives to tetrahydroquinolines. In addition, the strategy does not need the use of nitrogen protecting groups. Although one of the limitations is the 24‐hour reaction times in batch conditions, the use of flow conditions allows to obtain the products in just one hour.